Cold- and hot-water immersion are not more effective than placebo for the recovery of physical performance and training adaptations in national level soccer players - Gustafsson, J.; Montiel-Rojas, D.; Romare, M. G. A.; Johansson, E.; Folkesson, M.; Pernigoni, M.; Frolova, A.; Brazaitis, M.; Venckunas, T.; Ponsot, E.; Chaillou, T.; Edholm, P. (European Journal of Applied Physiology, 2025)
Purpose Cold- and hot-water immersion (CWI and HWI, respectively) are popular post-exercise recovery methods in competitive soccer. The aims of this study were to (1) compare the effect of post-exercise CWI, HWI and placebo on the recovery of physical performance in national level soccer players, and (2) investigate whether repeated use of these recovery modalities has an impact on training adaptations over a 15 week period.